2014
DOI: 10.1016/j.cattod.2013.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of ammonium ion in water with ozone over metal oxide catalysts

Abstract: Abstract3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 25 publications
(33 reference statements)
0
32
0
Order By: Relevance
“…Rare earth oxides (Faria et al 2009;Dai et al 2014), transition metal oxides (Ichikawa et al 2014;Turkay et al 2014), carbon materials Saleh and Gupta 2014;Wang 2015) and molecular sieve (Li et al 2014) are frequently used as catalysts. Among them, carbon-based materials, especially multi-walled carbon nanotubes (MWCNTs), have received increasing attention owing to its excellent characteristics, for example, (1) the high mesoporous area is favorable to the fluidity and mass transfer of reactants on catalyst surface; (2) the functional groups on MWCNTs surface are beneficial to their dispersion in water; (3) the resistance to abrasion and acidic/basic environments makes them suitable for intense oxidation circumstances, MWCNTs have been widely used as catalyst or catalyst support in wastewater treatment Gupta 2011, 2012b;Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth oxides (Faria et al 2009;Dai et al 2014), transition metal oxides (Ichikawa et al 2014;Turkay et al 2014), carbon materials Saleh and Gupta 2014;Wang 2015) and molecular sieve (Li et al 2014) are frequently used as catalysts. Among them, carbon-based materials, especially multi-walled carbon nanotubes (MWCNTs), have received increasing attention owing to its excellent characteristics, for example, (1) the high mesoporous area is favorable to the fluidity and mass transfer of reactants on catalyst surface; (2) the functional groups on MWCNTs surface are beneficial to their dispersion in water; (3) the resistance to abrasion and acidic/basic environments makes them suitable for intense oxidation circumstances, MWCNTs have been widely used as catalyst or catalyst support in wastewater treatment Gupta 2011, 2012b;Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalyst that usually applied for catalytic ozonation is metal oxide and cobalt oxide is one of them [9,[11][12][13].…”
Section: Pengaruh Suhu Kalsinasi Pada Cobalt Oksida Dan Kinerjanya Untukmentioning
confidence: 99%
“…However, mostly Co3O4 and CoO are used due to their stability [18,20]. These cobalt oxides were synthesized using various methods such as hydrothermal [21], precipitation [22][23][24], impregnation [13], femtosecond laser ablation [16], solid-state [14] and core-shell [15].…”
Section: Pengaruh Suhu Kalsinasi Pada Cobalt Oksida Dan Kinerjanya Untukmentioning
confidence: 99%
“…Ichikawa et al [12] studied a series of metal oxides catalysts’ (Fe 2 O 3 , CuO, Mn 3 O 4 , MgO, NiO, SnO 2 , Al 2 O 3 , Co 3 O 4 , ZnO) catalytic ozonation oxidation NH 4 + at 60 °C and without pH control of the solution. It was confirmed that MgO and NiO have the highest activity but low selectivity to gaseous products, while Co 3 O 4 has high selectivity to gaseous products but was slightly less active.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in presence of ozone, these transition metal oxides as catalysts have the ability to degrade NH 4 + in water. However, according to the previously mentioned [12], it is usually necessary to provide stronger reaction conditions (high temperature) due to the weak interaction between metal oxides and ozone. MeOH+normalO3Me+normalO2·+HO2 normalO2·+normalO3normalO3·+normalO2 normalO3·+normalH+HO3 HO3··OH+normalO2…”
Section: Introductionmentioning
confidence: 99%